PENERAPAN PERINSIP SYARIAH DALAM ASURANSI TAKFUL UMUM - A Asri (Jurnal Al-Fatih, 2019)
Sharia Banking and Insurance, is a new product of economic development in the special community of Muslims in Indonesia. This has become a legal problem that must be resolved in our country. This is very important to study, because both in the world of banking and insurance, especially by the wider community of some Muslims it is an understanding that is contrary to the principles of Islamic law, due to the nature of capitalism in operations from both are still very thick. The problem that will be examined in this paper is how is the Takaful law in Sharia Perspective? What is the form of takaful in general takaful insurance? How is the application of Sharia principles in general takaful insurance at PT. General Takaful Insurance Medan Branch. The purpose of this study is to find out Takaful law in the perspective of Sharia. To find out the form of Takaful in General Takaful. To find out the application of Sharia principles in General Takaful insurance at PT. General Takaful Insurance Medan Branch. The principle applied by general branch takaful insurance in accordance with the sharia principle is based on the principle of profit sharing (al-Mudharabah), which is to share the results of operational profits to all takaful participants who have never submitted a claim or canceled a policy. In this case the contract entered into between the company and the customer is the Tabarru Agreement, the Ta'awun Agreement, and the Wakalah Bil Ujrah Agreement. So that it can eliminate can eliminate gharar (uncertainty), Maisir (betting), and usury